Listening to the Powerless: Experiences of People with Severe Intellectual Disabilities in an Evangelical Church - Sarah Shea (Religions, 2019)
The experiences of people with severe intellectual disabilities (SID) in local churches are rarely studied, and their voices are not being heard in the research and religious communities. This study is an attempt to narrow the gap. Through a research method that combined person-centred care and action research, this study looks to explore the experiences of three persons with SID in a Hong Kong evangelical church, and give an account of the cultural and religious forces that have marginalized them. Findings show that it is not merely feasible but also necessary for church caregivers to listen to these powerless individuals if they want to be liberated from destructive stereotypical images of SID, broaden their basis of religious epistemology, and transform their spiritual care practices. However, the study reveals that there are some remaining barriers. It is found that the problematic evangelical style of spirituality has made Christians without disabilities misconceive individuals with SID as either inferior in the matter of faith or even incapable of coming to faith. Three corresponding types of pastoral responses that have kept persons with SID at the margins of the faith community are identified and discussed in this paper. The research results implies that evangelical Christian communities need nothing less than a critical examination of the logic of coming to faith if they want to remove such religious prejudice against persons with SID in future.